2023
DOI: 10.1097/sap.0000000000003321
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exogenous Testosterone on Breast Cancer Risk in Transmasculine Individuals

Abstract: Background Exogenous testosterone is vital to gender-affirming therapy for transmasculine individuals. Testosterone may be implicated in breast cancer (BCa) because it can activate androgen and estrogen receptors. To further explore this risk, we performed a systematic review to investigate the impact of exogenous testosterone on BCa risk in transmasculine individuals. Methods We searched PubMed/MEDLINE and Ovid/Embase for clinical and preclinical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…A recent systematic review about the impact of exogenous testosterone on BC risk in transmasculine people showed that, overall, transmasculine people had a lower incidence of BC compared with cisgender women, but they had a younger median age of presentation (47-50 vs 65-74 years). 43 Of note, these studies did not consistently specify whether cancer diagnosis occurred before or after gender-affirming mastectomy procedures.…”
Section: Reviewmentioning
confidence: 98%
“…A recent systematic review about the impact of exogenous testosterone on BC risk in transmasculine people showed that, overall, transmasculine people had a lower incidence of BC compared with cisgender women, but they had a younger median age of presentation (47-50 vs 65-74 years). 43 Of note, these studies did not consistently specify whether cancer diagnosis occurred before or after gender-affirming mastectomy procedures.…”
Section: Reviewmentioning
confidence: 98%